GEOCHEMISTRY OF LATE CRETACEOUS-PALEOGENE POTASSIC ROCKS OF THE EARLY EVOLUTIONARY STAGE IN THE KAMCHATKA ISLAND ARC - Flerov G.B.; Churikova T.G.; Fedorov P.I. (My University, 2001)
The first data are reported on the isotopic and trace-element composition of potassic igneous rocks from central Kamchatka. The composition of minerals and distribution of incompatible elements in volcanic (shoshonitic and potassic alkaline series) and intrusive (including differentiated gabbro-syenite and trachybasalt-latite pairs) rocks testify to the comagmatic character of members of the volcano-plutonic associations and the derivation of their parental melts from a single primary magma source. The low HFSE concentrations of the rocks, as compared with those of MORB, and their low Sr and high Nd isotopic ratios suggest that the mantle source was similar to MORB. The high LILE concentrations of the rocks point to the involvement of a fluid component, which was introduced into the melts during their primary magma evolution.
Keywords: Paleogene; Cretaceous; potassic rocks; Kamchatka; Кайнозой::Палеоген; Мезозой::Меловая; Cenozoic::Paleogene; Mesozoic::Cretaceous